The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00586-017-5076-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of Xpert MTB/RIF assay in the diagnosis of tubercular spondylodiscitis

Abstract: This study recommends Xpert MTB/RIF assay for early detection of Mycobacterium tubercular spondylodiscitis and Rifampicin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
1
22
1
1
Order By: Relevance
“…In this study, we have tried to find sensitivity and specificity of Gene Xpert in spinal tuberculosis cases, for which adequate literature data is not available yet. This is a prospective study and observed sensitivity of Gene Xpert is 91.18% and specificity is 100%, which correlates well with similar study by Held at al 25 showing sensitivity of 95.6% and specificity of 96.2% and for STB and study done by Arockiaraj et al 26 demonstrating sensitivity of 71.2% and specificity of 100% compared with composite reference standard. Positive predictive value is 100% and negative predictive value is 93.88% in our study, that is, negative result reliably excludes TB.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we have tried to find sensitivity and specificity of Gene Xpert in spinal tuberculosis cases, for which adequate literature data is not available yet. This is a prospective study and observed sensitivity of Gene Xpert is 91.18% and specificity is 100%, which correlates well with similar study by Held at al 25 showing sensitivity of 95.6% and specificity of 96.2% and for STB and study done by Arockiaraj et al 26 demonstrating sensitivity of 71.2% and specificity of 100% compared with composite reference standard. Positive predictive value is 100% and negative predictive value is 93.88% in our study, that is, negative result reliably excludes TB.…”
Section: Discussionsupporting
confidence: 90%
“…Our search yielded a total of 466 citations, 12 of which were finally included in the current meta-analysis based on the inclusion criteria ( Figure 1 and Table 1 ). 15 , 16 , 20 29 The included studies were published between 2014 and 2017. Data came from the People’s Republic of China, South Africa, India, and Indonesia, all of which are countries with high TB burden and low/middle income.…”
Section: Resultsmentioning
confidence: 99%
“…The CRS included all patients who have improved both clinically and radiologically after empirical antituberculous therapy where the results of culture, smear, and histology might be positive or negative for TB. 20 Moreover, the mean score of the 12 studies was 9.42 (range, 9–11) according to the criteria of QUADAS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies also used different culture references. Nine studies only used BACTEC MGIT 960 liquid culture as the reference, one study only used Lowenstein-Jensen solid culture as the reference [34], and four studies used both of them as references [18,22,24,35]. The performances of BACTEC MGIT 960 liquid and Lowenstein-Jensen solid cultures were different [54], which might also be one of the sources of heterogeneity among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled sensitivity of Xpert MTB/RIF was 96% (I 2 = 91%; 95% CI, 90-98). The specificity of Xpert MTB/RIF ranged from 17% (95% CI, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] to 100% (95% CI, 99-100) and the pooled specificity was 85% (I 2 = 97%; 95% CI, 57-96) ( Fig 4). As expected, the sensitivity was improved, and the specificity was undervalued when compared to the culture.…”
Section: Diagnostic Accuracy Of Xpert Mtb/rif Assay For Bjtbmentioning
confidence: 99%